2011
DOI: 10.1093/molehr/gar004
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1 complexes modulate sperm motility and present novel targets for male infertility

Abstract: Infertility is a growing concern in modern society, with 30% of cases being due to male factors, namely reduced sperm concentration, decreased motility and abnormal morphology. Sperm cells are highly compartmentalized, almost devoid of transcription and translation consequently processes such as protein phosphorylation provide a key general mechanism for regulating vital cellular functions, more so than for undifferentiated cells. Reversible protein phosphorylation is the principal mechanism regulating most ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 123 publications
2
60
0
Order By: Relevance
“…CG31467 was the top DE gene and plays a role in phosphatase binding and is expressed moderately in the adult testis of D. melanogaster (FlyBase). Protein phosphatases have been known to modulate sperm motility in mammals (Fardilha et al, 2011), and a gene encoding acylphosphatase (Acyp) has been found to be associated with HMS in F 1 and backcross hybrids between D. simulans and D. mauritiana (Michalak and Ma, 2008;Michalak and Noor, 2004). Octbeta3R is homologous to β-adrenergic receptors in vertebrates that play multifunctional roles in insects, and is an octopamine (Farooqui, 2012).…”
Section: Differential Gene Expressionmentioning
confidence: 99%
“…CG31467 was the top DE gene and plays a role in phosphatase binding and is expressed moderately in the adult testis of D. melanogaster (FlyBase). Protein phosphatases have been known to modulate sperm motility in mammals (Fardilha et al, 2011), and a gene encoding acylphosphatase (Acyp) has been found to be associated with HMS in F 1 and backcross hybrids between D. simulans and D. mauritiana (Michalak and Ma, 2008;Michalak and Noor, 2004). Octbeta3R is homologous to β-adrenergic receptors in vertebrates that play multifunctional roles in insects, and is an octopamine (Farooqui, 2012).…”
Section: Differential Gene Expressionmentioning
confidence: 99%
“…Moreover, the phosphorylation of the RVxF motif inhibits binding of PPP1CC2. This indicates the involvement of another protein phosphatase in the regulation of this interaction, the identity of which remains unknown, although a number of other nontype 1 protein phosphatases are known to be expressed in the testis (Fardilha et al 2011). Similarly, the kinase responsible for this phosphorylation remains in question.…”
Section: Ppp1cc2 Interacts With Tsks and Tssk1mentioning
confidence: 99%
“…Three genes are known to encode PP1 catalytic subunits, termed PP1a, PP1b, and PP1c, with diversity increased by alternative splicing (da Cruz e Silva et al, 1995b). PP1 regulates a variety of cellular events through the dephosphorylation of multiple substrates and its multifunctionality is due to its association with different regulators and/or targeting subunits (Bollen, 2001;Ceulemans and Bollen, 2004;Fardilha et al, 2010Fardilha et al, , 2011a known as PP1 Interacting Proteins (PIPs). The PP1 isoforms are highly conserved across their large catalytic domain, but are divergent at the N and C termini.…”
Section: Introductionmentioning
confidence: 99%
“…To exert their dephosphorylation reactions that are important in time and space, the diverse functions of PP1 must be independently regulated. For this reason, PIPs are believed to be much more specific for individual functions and are therefore better targets for specific pathways (Ceulemans and Bollen, 2004;Cohen, 2002;Fardilha et al, 2010Fardilha et al, , 2011aVirshup and Shenolikar, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation